Attitude towards retirement and financial preparation, perception of civil servants - Caroline Geetha; Vivin Vincent Chandran (Penerbit Universiti Malaysia Sabah, 2011)
Monetary Economics: Issues and Challenges provides the insights of monetary economics. The book would enable readers to understand the latest development in the banking sector. The latest development covers Islamic finance, retirement planning tools and Bank Negara’s Reserve Requirement Policies. The book would be a need for students in the area of finance and for investors to keep themselves updated on the latest development related to monetary issues.